Mental health, burnout and resilience in community pharmacists during the COVID-19 pandemic: A cross-sectional study - Zeana Samir AlKudsi; Nadin Hany Kamel; Alla El-Awaisi; Mujahed Shraim; Maguy Saffouh El Hajj (Elsevier, 2022)
Background: The study aimed to assess burnout, resilience, and levels of depression, anxiety, stress and fear among community pharmacists during the pandemic, and examine if fear of COVID-19 is associated with these outcomes of interest. Methods: A cross-sectional survey of community pharmacists in Qatar was conducted. Pharmacists' burnout was measured by the Maslach Burnout Inventory: Human Services Survey for Medical Personnel (MBI-HSS™ for MP-Mindgarden). Resilience was assessed using the Connor-Davidson Resilience Scale-10 (CD-RISC-10). Depression, anxiety, and stress were measured by the Depression, Anxiety, and Stress Scale (DASS-21). Fear of COVID-19 was assessed by the Fear of COVID-19 Scale (FCV-19S). Results: 256 respondents completed the survey and were included in the final study analysis (response rate: 42.7%). Overall, participants reported a moderate level of burnout as illustrated in the mean scores of the three burnout dimensions; 20.54 (SD = 12.37) for emotional exhaustion, 6.76 (SD = 6.22) for depersonalization, and 36.57 (SD = 9.95) for personal accomplishment. Moreover, depression, anxiety and stress were reported by 44.8%, 53.2% and 25.4% of particiants respectively. Participants had shown moderate resilience (mean score: 27.64 (SD = 8.31)) and their mean score fear of COVID19 was 15.67 (SD = 6.54). Fear of COVID-19 was a statistically significant and an independent predictor of depression, anxiety, and stress levels. Conclusions: The pharmacists experienced moderate burnout but moderate resilience, which indicates their potential to overcome difficulties. Future interventions at the personal, national and organizational levels are required to enhance the pharmacists' wellbeing by decreasing stress, improving self-efficacy and resilience, and preventing burnout.